Oxidative stress as a converging mechanism of aging and neurodegeneration: From molecular pathways to therapeutic targets - Faradilla, Meutia A.; Anastasya, Karina S.; Yastani, Deasyka; Yohana, Yohana; Tungka, Endrico X.; Suweino, Suweino (Narra Sains Indonesia, 2026)
Aging is the primary risk factor for major neurodegenerative disorders, yet the precise molecular links between biological aging and progressive neuronal loss remain complex. Oxidative stress, defined as an imbalance between the production of reactive oxygen species (ROS) and antioxidant defenses, has emerged as a central converging mechanism driving both processes. This review aims to synthesize current evidence demonstrating how chronic redox imbalance drives cellular senescence and neuronal vulnerability through mitochondrial dysfunction, lipid peroxidation, and oxidative protein damage. These insights underscore how sustained oxidative insults promote the misfolding and aggregation of disease-defining proteins, including amyloid-beta in Alzheimer’s disease and α-synuclein in Parkinson’s disease, thereby amplifying neuroinflammation, synaptic dysfunction, and bioenergetic failure. Furthermore, antioxidant-based therapeutic strategies are critically reassessed, highlighting a paradigm shift from non-specific radical scavenging toward targeted modulation of endogenous defense systems, particularly NRF2 signaling and mitochondria-directed antioxidants. By integrating molecular mechanisms with translational perspectives, this review integrates molecular, cellular, and translational evidence to explain how oxidative stress links biological aging to neurodegenerative disorders such as Alzheimer’s and Parkinson’s diseases.